Camping with Jesus: Theologically Reflecting on Evangelical Christian Festivals - Helen Collins (Religions)
Attending a Christian summer camp or festival is a regular feature of many evangelical church calendars within the UK. This article uses a practical theology approach to explore definitions and distinctives of evangelical camping, both within the literature on evangelical camping and through examining the websites and publicity materials of three specific camps—New Wine, Big Church Festival and Newday Generation. The analysis highlights the significance placed upon the location, size, rhythms and purposes of gathering in the festivals’ self-understandings. This leads into a theological reflection upon the biblical festival of Sukkot to examine the ways in which God’s work might be disclosed through the practice of evangelical camping. Three pairs of themes emerge from the comparison: located and temporal, secular and religious, and rejoicing and re-examining. These themes are drawn upon to propose ways in which God might be at work in the social world disrupting a sense of permanence, blurring the boundaries between faith and the world, and calling people into radical solidarity with creation and with the marginalized. Finally, suggested actions are proposed as to how evangelical festivals may better respond to God’s disclosure.